Genetic and Biochemical Studies with Chinese Hamster Ovary Cell Mutants Resistant to the Purine Nucleoside Analogs: Toyocamyin, Formycin A and Formycin B - Mehta, Kamal D. (My University, 1985)
The aim of this study was to investigate the mechanism of cellular resistance and toxicity to the purine nucleoside analogs toyocamycin, formycin A and formycin B by using genetic, biochemical and immunological approaches.
To investigate the similarity or differences in the mechanism of action of various pyrrolopyrimidine nucleosides, second-step toyocamycin resistant mutants (Toyʳᴵᴵ mutants) of Chinese hamster ovary cells were isolated from a cell line which exhibited similar degree of resistance to toyocamycin and tubercidin. These second-step mutants exhibited a further 8- to 9-fold increase in resistance to toypcamycin but no concurrent increase in their resistance towards tubercidin. The Toyʳᴵᴵ mutants were found to be very similar to the first-step mutants in their levels of adenosine kinase activity (< 1%), as well as cellular uptake and phosphorylation of adenosine and its analogs. The increased resistance of the Toyʳᴵᴵ mutants to toyocamycin but not to tubercidin provides strong evidence that the mechanism of cellular toxicity of these two analogs is different and suggests that these mutants may be affected in a cellular component which is specifically involved in the toxicity of toyocamycin. The Toyʳᴵᴵ mutants also exhibit increased resistance to sangivamycin and the tricyclic pentaazaacenaphthylene ribonucleoside, indicating that the mechanism of cellular toxicity of these two analogs may be similar to that of toyocamycin.
The genetic and biochemical approach was also used to investigate the mechanism of resistance and metabolism to another group of nucleoside analogs in which the base is linked to ribose moiety by a C-C linkage. Studies presented showed that stable mutants which are approximately 3- and 8-fold resistant to the C-nucleoside, formycin A (Fomᴿ mutants) could be obtained in a single step in CHO cells. In cell extracts, the Fomᴿ mutants contained no measurable activity of the enzyme adenosine kinase. In cell hybrids formed between formycin A resistant and sensitive cells (Fomˢ) as well as formycin A resistant and toyocamycin resistant cells (Toyʳ), the drug resistant phenotype of Fomᴿ mutants behaved codominantly as indicated by the degree of resistance of the hybrid cells to formycin B. However, extracts from these hybrid cells contained either≈50% (Fomᴿ x Fomˢ) or <1% (Fomᴿ x Toyʳ) AK activity indicating that the lesion in these mutants neither suppresses the wild-type AK activity nor complements the AK deficiency of the Toyʳ mutants. Cross-resistance studies with various adenosine analogs show that these mutants are distinct from the Toyʳ mutants, which also contained no measurable AK activity in cell extracts. The Fomᴿ mutants exhibited a high degree of cross-resistance to different C-nucleosides but did not show appreciable cross-resistance to different N-nucleosides examined. In contrast, mutants selected in presence of toyocamycin exhibited a high degree of cross-resistance to both N- as well as C-nucleosides which are phosphorylated via adenosine kinase. Studies on the cellular uptake and phosphorylation of radiolabelled N- and C-nucleosides by various mutant lines showed that, unlike the Toyʳ mutants which show greatly reduced phosphorylation of all adenosine analogs (both N- and C-nucleosides), the Fomᴿ mutants showed reduced cellular phosphorylation of only C-nucleosides but not of N-nucleosides. The normal level of phosphorylation of N-nucleosides in the Fomᴿ mutants suggested that the Fomᴿ mutants contain normal levels of AK activity in vivo. The above observations together with the specific cross-resistance of these mutants to C-nucleosides as well as the reduced phosphorylation of such nucleosides, provides strong suggestive evidence that the Fomᴿ mutants contain a novel genetic lesion affecting adenosine kinase which specifically affects the phosphorylation of only C-purine nucleosides.
Since formycin A under the normal cell culture condition is rapidly deaminated to the inosine analog, formycin B, cellular toxicity and resistance of formycin B was also investigated. Mutants of CHO cells selected for resistance to formycin B (Fomʳ mutants) were found to be 5- to 8-fold resistant to this drug. Cross-resistance studies with these mutants revealed that they exhibit increased resistance to all adenosine analogs (N- and C-nucleosides); as well as reduced cellular uptake and phosphorylation. However, unlike the Fomᴿ and Toyʳ mutants, which contained no AK activity in their cell extracts, the Fomʳ mutants were found to contain between 60 - 110% of WT activity in their cell extracts. The AK activity present in both Fomʳ mutant cell extracts differed from the WT AK activity in terms of its specific activity as well as in its ability to phosphorylate adenosine analogs. The AK activity from the Fomʳ mutants was found to have less affinity for phosphorylation of the formycin A derivative, Bbb-85. Like Toyʳ mutants, Fomʳ mutants were found to show recessive-behaviour in cell hybrids.
Biochemical studies on the metabolism of formycin B indicated that upon incubation with CHO cells, [³H]formycin B is metabolized into formycin B-5'-monophosphate, formycin A-5'-monophosphate and higher phosphorylated derivatives of formycin A which are incorporated into RNA. All three different classes of mutants affected In AK exhibit appreciable cross-resistance as well as reduced cellular uptake and phosphorylation of formycin B. These observations strongly indicate that in CHO cells, formycin B is phosphorylated via AK and like other nucleoside analogs, its phosphorylation is essential for the cellular toxicity. Formycin B-5'-monophosphate and formycin A-5'-monophosphate have been found to inhibit the purine nucleotide biosynthetic enzyme adenylosuccinate synthetase.
To gain further insight into the nature of genetic and biochemical alterations in different types of mutants affected in adenosine kinase, this enzyme from CHO cells was purified to homogeneity. Antibodies which specifically cross-react with adenosine kinase have been raised. Immunoblot analyses using these antibodies showed that all three classes of mutants i.e., Toyʳ, Fomᴿ and Fomʳ contained nearly similar amounts of cross-reacting material that had a similar electrophoretic mobility to the enzyme in the WT cells. These results indicate that the lesion in these mutants does not involve a deletion or regulatory type of genetic alteration in the AK gene nor a nonsense type of mutation which may cause premature chain termination. Instead, these mutants may contain a missense type of alteration in the structural gene of AK. Using these antibodies, regions (or spots) on two-dimensional gels that correspond to the AK protein have been identified. Comparison of the 2-D gel electrophoretic patterns of total cellular proteins from different-mutant lines indicates that some of the mutants show a specific alteration in this region. This supports the inference that these mutants may contain a missense type of mutation in the structural gene of AK.
The results presented in this thesis have been presented or submitted in the following publications.
1. Mehta, K.D. and Gupta, R.S. (1983) Formycin B-Resistant Mutants of Chinese Hamster Ovary Cells: Novel Genetic and Biochemical Phenotype Affecting Adenosine Kinase. Mol. Cell. Biol. 3, 1468.
2. Gupta, R.S. and Mehta, K.D. (1984) Genetic and Biochemical Studies on Mutants of CHO Cells Resistant to 7-Deazapurine Nucleosides: Differences in the Mechanisms of Action of Toyocamycin and Tubercidin. Biochem. Biophys. Res. Commun. 120, 88.
3. Mehta, K.D. and Gupta, R.S. Novel Mutants of Adenosine Kinase Specifically Affected in the Phosphorylation of C-Nucleosides. Manuscript submitted to FEBS Lett.
4. Mehta, K.D. and Gupta, R.S. Metabolism and the Mechanism of Action of Formycin B in Chinese Hamster Ovary Cells: Involvement of Adenosine Kinase in Drug Phosphorylation. Manuscript submitted to J. BioI. Chem.
Keywords: Biochemistry; Biochemistry